Melatonin in Semen Extender Improves Freezability in Mithun - Perumal, P. (International Journal of Bio-resource and Stress Management, 2019)
Melatonin plays important roles in circadian clock regulation and seasonal reproduction in mammals. It is also a potential antioxidant and anti-apoptotic agent in semen preservation. Season/climatic factors/photoperiod and temperature humidity index is one of the most important factors, effect on the variation in semen quality parameters (SQPs) and fertility rate. The present study was conducted to assess the effect of melatonin (MT) on SQPs at different seasons of the year such as sperm motility, viability, total sperm abnormality, intactness of acrosome, functional plasma membrane and nuclear integrity in mithun. A total numbers of 80 ejaculates (20 ejaculates in each season) were collected twice per week from mithun bulls by transrectal massage method and semen sample was divided into six equal aliquots and diluted with the Tris egg yolk citrate glycerol extender (TEYCGE). Group 1: semen without additives (control), group 2 to 6: semen was diluted with 1, 2, 3, 4 and 5 mM of melatonin, respectively. These SQPs were estimated in frozen thawed semen. Inclusion of melatonin into the diluent resulted in significantly (p<0.05) decreased dead and abnormal spermatozoa percentage and acrosomal abnormalities whereas significant improvement was observed in the sperm motility, viability, plasma membrane and nuclear integrity in treatment as compared to control group at different seasons of the year. The present study result clearly indicated that melatonin protected the post thaw SQPs in different seasons and also semen quality varied from different seasons and was significantly higher in spring and lowest was in summer season.